Little big world : collecting Louis Marx and the American fifties - Hammond, Jeffrey, 1950- (Sightline books., 2010)
"Collections are more about who one is than about what is collected. In Little Big World, Jeffrey Hammond's resonant 1950Æs inner child speaks through the reflective sixty-something man about the culture and magic of a spectrum of action figure playsets through a lifetime."ùMarilynn Gelfman Karp, author, In Flagrante Collecto